A step-coated AB2-based composite hydrogen storage alloy, its preparation method and application
Patent Information
- Application Number
- CN202610952751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-11-03
AI Technical Summary
In the field of efficient hydrogen storage material technology, the existing hydrogen storage alloys face the challenge of improving the application of existing materials and addressing the performance limitations of existing hydrogen storage materials, making it difficult to simultaneously meet the requirements of high capacity, easy activation, long lifespan, and low cost in composite hydrogen storage alloys.
A stepwise coated AB2-based composite hydrogen storage alloy is adopted. By using AB2-based composite hydrogen storage materials as the matrix and sequentially coating BCC alloy and AB5 alloy as catalysts, three technical methods are used to solve the technical problems of existing hydrogen storage materials.
This technology enables the application of efficient and low-cost hydrogen storage materials, solves the technical problems of existing hydrogen storage materials, and provides a solution for the application of efficient and low-cost hydrogen storage materials.
Smart Images

Figure CN123024880A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallic solid hydrogen storage materials technology, specifically to a stepwise coated AB2-based composite hydrogen storage alloy, its preparation method and application, and more particularly to an AB2-based composite hydrogen storage alloy consisting of stepwise coatings of BCC alloy and AB5 alloy, its preparation method and application. Background Technology
[0002] Hydrogen energy is considered an ideal clean energy carrier due to its abundant resources, high energy density, and pollution-free nature. In hydrogen energy applications, hydrogen storage and transportation are crucial. Among solid-state hydrogen storage methods, metal hydride storage offers advantages such as high safety and high volumetric hydrogen storage density. Currently, researchers have developed various types of hydrogen storage alloys, but existing mainstream hydrogen storage alloys each have performance limitations, making it difficult to simultaneously meet the comprehensive requirements of high capacity, easy activation, long lifespan, and low cost.
[0003] AB2-type TiMn2-based Laves phase hydrogen storage alloys possess advantages such as high hydrogen storage capacity (theoretically >2.0 wt%), moderate cost, and good room-temperature reversibility, making them a promising candidate material for large-scale solid-state hydrogen storage applications. However, these alloys face a significant challenge in practical applications: activation is difficult, typically requiring more than 20 activation cycles to reach saturation capacity. Furthermore, the severe lattice distortion during hydrogen absorption and desorption cycles in AB2 alloys leads to rapid long-term capacity decay, hindering their large-scale application.
[0004] AB5 type LaCe rare earth hydrogen storage alloy has the advantages of excellent room temperature activation performance, strong resistance to poisoning and good kinetic performance, but its upper limit of mass hydrogen storage capacity is only 1.4 to 1.6 wt%, and the cost of rare earth raw materials is high, so it cannot be used as a large-capacity solid hydrogen storage material on its own.
[0005] Vanadium-based body-centered cubic (BCC) hydrogen storage alloys possess extremely high theoretical hydrogen storage capacity, with a hydrogen mass fraction exceeding 3.8%. However, the surface of these alloys is highly susceptible to oxidation by air, forming a dense passivation film, and the activation temperature is typically above 300°C. Furthermore, vanadium-based alloys exhibit poor resistance to impurity poisoning, and the high cost of vanadium-containing alloys further limits their practical applications.
[0006] To address the performance limitations of single alloys, attempts have been made to achieve complementary performance through the composite of different types of alloys. For example, patent document CN114619026A discloses a solid hydrogen storage material formed by island-like coating of an AB2 type hydrogen storage alloy with an AB5 type hydrogen storage alloy. This scheme achieves the combination of the two types of alloys through physical adsorption, improving the activation performance of the AB2 alloy. Another example is patent document CN113528922A, which discloses a method for preparing AB2-AB5 composite hydrogen storage materials by coating the surface of AB2 type hydrogen storage alloy particles with an AB5 alloy using a binder, followed by vacuum drying and high-temperature cladding (1300–1400℃). Kumar et al. (Journal of Alloys and Compounds 2015, 649, 801e808) reported a composite hydrogen storage material prepared with TiMn2 as the secondary phase and BCC as the main phase, finding that adding TiMn2 can increase the plateau pressure of the composite material and reduce the hydride decomposition temperature. Yu et al. (Appl. Phys. Lett. 2005, 87, 133121) achieved a high initial discharge capacity by ball milling AB5 nanoparticles onto the surface of a BCC alloy. However, the above methods are all binary composites of two types of alloys, and there is still room for improvement in simultaneously improving activation performance, enhancing cycle stability, and controlling costs.
[0007] Therefore, there is an urgent need to develop a composite hydrogen storage alloy that can balance high capacity, easy activation, long lifespan, and low cost, as well as its preparation method. Summary of the Invention
[0008] The purpose of this application is to provide a stepwise coated AB2-based composite hydrogen storage alloy and its preparation method. By using AB2 alloy as the matrix and sequentially coating it with BCC alloy and AB5 alloy, the advantages of the three types of alloys are complemented, solving the technical problem that existing hydrogen storage alloys cannot simultaneously achieve high capacity, easy activation and long life.
[0009] To achieve the above objectives, this application provides the following technical solution: A step-coated AB2-based composite hydrogen storage alloy includes a matrix and an island-shaped coating layer; the matrix is an AB2 alloy; the island-shaped coating layer is composed of a BCC alloy and an AB5 alloy; wherein the BCC alloy partially or completely fills the surface defects of the matrix.
[0010] This application also provides the following technical solutions: The aforementioned method for preparing the stepwise coated AB2-based composite hydrogen storage alloy includes the following steps: S1. AB2 alloy powder and BCC alloy powder are mixed, pulverized and heat-treated sequentially under an inert atmosphere to obtain AB2@BCC composite powder; the heat treatment is carried out at a temperature lower than the melting points of the AB2 alloy and BCC alloy respectively. S2. The AB2@BCC composite powder and AB5 alloy powder are mixed, pulverized and heat-treated sequentially under an inert atmosphere to obtain the stepwise coated AB2-based composite hydrogen storage alloy powder; the heat treatment is carried out at a temperature lower than the melting points of the AB2 alloy, BCC alloy and AB5 alloy.
[0011] This application provides the following technical solution: The aforementioned step-coated AB2-based composite hydrogen storage alloy is used in the field of hydrogen storage.
[0012] The technical solution provided in this application has the following beneficial effects: (1) The composite hydrogen storage alloy provided in this application uses an AB2-type alloy as the matrix, a BCC alloy as the defect-filling functional component, and an AB5 alloy as the catalytic activation functional component to form a synergistic hierarchical island-like coating structure. Among them, the BCC alloy fills the surface defects of AB2, buffers the hydrogen absorption volume expansion, and inhibits cycle pulverization; the AB5 alloy provides a large number of surface catalytic active sites, which can rapidly crack hydrogen at room temperature and significantly reduce the number of activations. In the composite hydrogen storage alloy, the three types of alloys each retain the independent crystalline structure of the Laves phase, the BCC solid solution phase, and the CaCu5 phase, thereby achieving a synergistic improvement in hydrogen storage capacity, activation performance, and cycle stability.
[0013] (2) The composite hydrogen storage alloy provided in this application can be activated as low as 5 times, with a hydrogen absorption capacity of 1.90 to 1.95 wt% and a capacity retention rate of not less than 98.5% after 100 cycles, thus taking into account excellent activation performance, high hydrogen storage capacity and excellent cycle stability. At the same time, using low-cost AB2 alloy as the matrix, only a small amount of BCC (2 to 6 wt%) and AB5 (1 to 4 wt%) are added as coating layers, and the raw material cost is only about 10 to 20% higher than that of pure AB2 alloy, thus taking into account both hydrogen storage performance and economy.
[0014] (3) The preparation method provided in this application adopts a stepwise composite and two-step low-temperature annealing process design, combined with gradient particle size control. First, BCC micro powder (8~10 μm) is mixed and ground with AB2 matrix (80~300 μm). The particle size difference allows BCC micro powder to preferentially embed into the pits and defects on the surface of AB2 matrix. Then, low-temperature annealing causes interfacial atomic interdiffusion between BCC alloy and AB2 alloy, achieving metallurgical bonding without melting the two phases, thus obtaining AB2@BCC composite powder. Subsequently, finer AB5 ultrafine powder (≤3 μm) is added for secondary mixing and grinding, and then low-temperature annealing allows AB5 ultrafine powder to stably adhere to the AB2@BCC surface. The two-step low-temperature annealing effectively avoids the phase structure damage and excessive element diffusion problems caused by conventional high-temperature melting composite or high-temperature cladding. The preparation method has the advantages of mild process conditions and controllable operation, and is suitable for industrial mass production.
[0015] (4) The composite hydrogen storage alloy provided in this application can be used in fields such as hydrogen energy storage and transportation, solid hydrogen storage in hydrogen refueling stations, and hydrogen purification. It is especially suitable for solid hydrogen storage application scenarios with high requirements for the activation performance and cycle life of hydrogen storage materials, providing a feasible technical solution for the large-scale application of hydrogen storage materials. Attached Figure Description
[0016] Figure 1 The image shows the SEM image of the AB2@BCC@AB5 composite hydrogen storage alloy obtained in Example 1.
[0017] Figure 2 The image shows the XRD pattern of the AB2@BCC@AB5 composite hydrogen storage alloy obtained in Example 1. Invention Details 1. Terminology Explanation All patents and other publications cited herein are incorporated herein in their entirety. In the event of any conflict between any description of terminology herein and any document incorporated herein by reference, this document shall prevail.
[0019] Numerical ranges can be represented by a hyphen "-" or a tilde "~". Unless otherwise stated, the range should be understood to encompass both the endpoint values and any values in between. There are no particular restrictions on the type of numeric values within the range, including but not limited to integers, decimals, fractions, percentages, etc., unless explicitly excluded by the context or a particular numeric type is technically unavailable. The type of numeric values within the range is not limited by the specific representation of the endpoints.
[0020] The terms “including,” “containing,” and similar expressions have a non-restrictive meaning.
[0021] "Optional" is used to indicate that a certain feature (including but not limited to components, steps, parameters or structures) may be present in some embodiments, but may not appear in other embodiments, thereby providing technical flexibility for different implementations without departing from the core concept of the present invention.
[0022] "Any combination" of the enumeration items means any two or more of the enumeration items that coexist or are used together, including but not limited to any two combinations, any three combinations, any more items, and combinations of all the enumeration items, unless the context explicitly excludes it or a particular combination is technically impossible.
[0023] The use of labels such as a), b), i), ii), 1), 2), S1, S2, etc. to number the steps of a method is only for the convenience of description and reading, and does not mean that the corresponding steps must be performed in the order of the numbers, unless the text explicitly states or the information in the text can be clearly inferred that there is a logical or temporal relationship between specific steps.
[0024] The use of ordinal terms such as “first” and “second” to distinguish elements with the same name (e.g., first intermediate, second intermediate) does not necessarily indicate that any element has any priority, order, or hierarchy relative to another required element, but is merely used as a marker.
[0025] The "hydrogen storage alloy" described in this article refers to an alloy material capable of reversibly absorbing and releasing hydrogen under certain temperature and hydrogen pressure conditions. In this alloy, hydrogen is typically adsorbed / dissolved in the interstitial crystal lattice in an atomic state and can form a metallic hydride phase.
[0026] The “island-like coating” mentioned in this article refers to a discontinuous coating structure attached to the surface of an alloy substrate, consisting of multiple spaced-apart particles and / or micro-regions.
[0027] As used herein, "surface defects" refers to microscopically uneven areas on the surface of an alloy matrix. For example, surface defects include, but are not limited to, surface depressions, pits, pores, microcracks, scratches, and other areas that increase surface roughness and / or reduce surface integrity.
[0028] The "AB2 alloy" described in this article refers to a hydrogen storage alloy composed of A-side elements and B-side elements, with an atomic molar ratio of approximately 1:2 between the A-side elements and B-side elements. The A-side elements are metallic elements with a strong affinity for hydrogen and readily form hydrides, typically including one or more elements such as Ti and Zr. The B-side elements are transition metal elements capable of forming alloy phases with the A-side elements, typically including one or more elements such as Mn, Cr, Fe, Ni, and Co. The AB2 alloy typically has a Laves phase as its main constituent phase, including but not limited to C14, C15, C36 types, and their mixed structures. In this article, the subscripts following each element in the general chemical formula of the AB2 alloy indicate the designed molar ratio of the corresponding element, and reasonable deviations due to batching errors, element burn-off, or analytical errors are allowed.
[0029] The term "BCC alloy" as used herein refers to a hydrogen storage alloy possessing a body-centered cubic (BCC) crystal structure and with the BCC solid solution phase as the predominant crystalline phase. As an example, a BCC alloy can be composed of V and two or more elements selected from Ti, Zr, Nb, Mo, Hf, Cr, Fe, and Mn. In this document, the subscripts following each element in the general chemical formula of a BCC alloy indicate the designed molar ratio of the corresponding element, and deviations due to batching errors, element burn-off, or analytical errors are permissible.
[0030] The "AB5 alloy" described in this article refers to a hydrogen storage alloy composed of A-side elements and B-side elements, with an atomic molar ratio of approximately 1:5 between the A-side elements and B-side elements. The A-side elements typically include one or more rare earth elements such as La, Ce, Pr, and Nd; the B-side elements typically include one or more elements such as Ni, Co, Mn, Al, Fe, and Cu. The AB5 alloy typically has a CaCu5-type hexagonal structure as its main constituent phase. In this article, the subscripts following each element in the chemical formula of the AB5 alloy indicate the designed molar ratio of the corresponding element, and deviations caused by batching errors, element burn-off, or analytical errors are permissible.
[0031] The term "heat treatment" as used herein refers to the thermal process of heating, holding, and cooling alloy materials. This heat treatment is used to regulate the microstructure and properties of alloy materials, including but not limited to reducing or eliminating residual stress, improving microstructure uniformity, adjusting phase composition, enhancing structural stability, and improving mechanical properties. Exemplary heat treatments include, but are not limited to, annealing, normalizing, quenching, tempering, solution treatment, aging treatment, and stress relief treatment. Annealing refers to a heat treatment method in which the alloy is heated to a predetermined temperature and held at that temperature, followed by a relatively slow cooling process, such as furnace cooling or controlled temperature slow cooling, to reduce residual stress and stabilize the microstructure.
[0032] The "vacuum induction melting" described in this article refers to a process for melting and alloying alloy raw materials in a vacuum induction melting furnace. Specifically, the alloy raw materials are placed in a vacuum induction melting furnace, and the furnace chamber is evacuated to reduce the content of gaseous impurities. Then, a protective gas (such as argon) is introduced to a predetermined pressure, and the alloy raw materials are melted using electromagnetic induction heating, achieving mixing and alloying of the components in the molten state. Vacuum induction melting can reduce the content of gaseous impurities such as oxygen, nitrogen, and hydrogen in the melt, and reduce the oxidation or volatilization of alloying elements during high-temperature melting, thereby facilitating the acquisition of alloy materials with uniform composition.
[0033] The term "pulverization" as used in this article refers to processing methods that reduce the particle size of solid materials by applying external forces to break, grind, or disperse them. Pulverization includes, but is not limited to, crushing, grinding, and powder classification. Crushing refers to the process of coarsely crushing larger lumps of material to a certain particle size range; grinding refers to the process of further refining materials to micron or submicron-sized powders using grinding media or abrasive action, including but not limited to ball milling, roller milling, hammer milling, and vibratory milling; powder classification refers to the process of separating and screening the pulverized powder according to particle size, including but not limited to conventional classification methods such as sieving, air classifying, and centrifugal classification. Pulverization can be carried out under dry (without additional liquid media) or wet conditions. Sieving refers to classifying the pulverized powder by passing it through a sieve with a specified mesh size.
[0034] The term "hydrogen absorption capacity" as used in this article refers to the percentage of hydrogen mass absorbed by a unit mass of hydrogen storage alloy under certain temperature and hydrogen pressure conditions, expressed in wt% (mass percentage). Hydrogen absorption capacity is one of the core performance indicators for evaluating the hydrogen storage capacity of hydrogen storage alloys. Its value is calculated using a pressure-composition-isothermal (PCT) testing system based on the ideal gas law (N=PV / RT) and the change in gas pressure during hydrogen absorption.
[0035] The “metal solid hydrogen storage tank” mentioned in this article refers to a closed container that uses a hydrogen storage alloy as the hydrogen storage medium and achieves hydrogen storage and release through the reversible reaction between the alloy and hydrogen.
[0036] The “stationary hydrogen energy storage system” mentioned in this article refers to a hydrogen energy storage device that is fixedly installed in a specific location (such as a hydrogen refueling station, a renewable energy power plant, an industrial park, etc.) for the large-scale storage and peak-shaving supply of hydrogen.
[0037] The term "mobile hydrogen-powered vehicle" as used in this article refers to a mobile transportation vehicle powered by hydrogen, including but not limited to new energy vehicles, hydrogen fuel cell vehicles, hydrogen forklifts, hydrogen ships, hydrogen trains, and hydrogen aircraft.
[0038] The "hydrogen purification device" described in this article refers to a device that utilizes the selective absorption characteristics of hydrogen by hydrogen storage alloys to separate and purify hydrogen from a hydrogen-containing gas mixture. The hydrogen storage alloy absorbs only hydrogen and absorbs very little or no other gases (such as N2, CH4, CO, etc.), and hydrogen purification can be achieved through a hydrogen absorption / desorption cycle.
[0039] The "hydrogen compression storage device" mentioned in this article refers to a device that utilizes the principle of hydrogen storage alloy to absorb hydrogen at a lower pressure and release high-pressure hydrogen at a higher temperature to achieve hydrogen pressurization and storage.
[0040] The "portable hydrogen power source" mentioned in this article refers to a small, lightweight hydrogen power supply device that can be carried or moved around, and is often used in field operations, emergency rescue and disaster relief, military equipment and other scenarios.
[0041] The "power grid peak shaving hydrogen energy storage system" mentioned in this article refers to a system that uses hydrogen energy storage technology to shave peaks and fill valleys in the power grid. Typically, during periods of low electricity demand, surplus electricity is used to produce and store hydrogen, and during periods of high electricity demand, the hydrogen is fed back to the power grid through fuel cells or combustion turbines to generate electricity.
[0042] The "integrated renewable energy hydrogen production and storage system" mentioned in this article refers to a comprehensive energy system that integrates functions such as renewable energy power generation (solar and wind power), hydrogen production through water electrolysis, hydrogen storage, and fuel cell power generation.
[0043] 2. Implementation Plan One embodiment of this application is as follows: A step-coated AB2-based composite hydrogen storage alloy includes a matrix and an island-shaped coating layer; the matrix is an AB2 alloy; the island-shaped coating layer is composed of a BCC alloy and an AB5 alloy; wherein the BCC alloy partially or completely fills the surface defects of the matrix.
[0044] In some specific implementations, the A-side element of the AB2 alloy is Ti, Zr, or any combination thereof, and the B-side element is Mn, Cr, Fe, Ni, Co, or any combination thereof.
[0045] In some specific implementations, the BCC alloy is composed of V and any two or more of Ti, Zr, Nb, Mo, Hf, Cr, Fe, and Mn.
[0046] In some specific implementations, the A-side element of the AB5 alloy is La, Ce, Pr, Nd or any combination thereof, and the B-side element is Ni, Co, Mn, Al, Fe, Cu or any combination thereof.
[0047] In some specific implementations, the general chemical formula of the AB2 alloy is Ti. (1-x) Zr x Mna Cr b Fe c Where, 0.10≤x≤0.30, 0.80≤a≤1.20, 0.60≤b≤0.90, and 0.05≤c≤0.15.
[0048] In some specific implementations, the general chemical formula of the BCC alloy is Ti. α Cr β V γ Where, 0.3≤ α ≤0.4, 0.22≤ β ≤0.30, 0.30≤ γ ≤0.50.
[0049] In some specific implementations, the general chemical formula of the AB5 alloy is La. (1 p) Ce p Ni t Co u Mn v Al w Where, 0.2≤ p ≤0.3, 3.8≤ t ≤4.2, 0.3≤ u ≤0.4, 0.3≤ v ≤0.4, 0.15≤ w ≤0.25.
[0050] In some specific implementations, the content of the AB2 alloy in the composite hydrogen storage alloy is 90-97 wt%; the content of the BCC alloy in the composite hydrogen storage alloy is 2-6 wt%; and the content of the AB5 alloy in the composite hydrogen storage alloy is 1-4 wt%.
[0051] Another implementation scheme of this application is as follows: The preparation method of any of the aforementioned stepwise coated AB2-based composite hydrogen storage alloys includes the following steps: S1. AB2 alloy powder and BCC alloy powder are mixed, pulverized and heat-treated sequentially under an inert atmosphere to obtain AB2@BCC composite powder; the heat treatment is carried out at a temperature lower than the melting points of the AB2 alloy and BCC alloy respectively. S2. The AB2@BCC composite powder and AB5 alloy powder are mixed, pulverized and heat-treated sequentially under an inert atmosphere to obtain the stepwise coated AB2-based composite hydrogen storage alloy powder; the heat treatment is carried out at a temperature lower than the melting points of the AB2 alloy, BCC alloy and AB5 alloy respectively. The weight ratio of the AB2 alloy powder, BCC alloy powder and AB5 alloy powder is (90-97):(2-6):(1-4), preferably 95:3:2, 92:5:3, 94:4:2, 90:6:4 or 97:2:1; The maximum particle size of the AB2 alloy powder is no more than 500 μm; the D50 of the BCC alloy powder is 8-10 μm; and the D50 of the AB5 alloy powder is no more than 3 μm.
[0052] In some specific embodiments, the AB2 alloy powder, BCC alloy powder, and AB5 alloy powder are obtained by the following methods: S01. The alloy raw materials are vacuum induction melted and shaped to obtain AB2 alloy billet, BCC alloy billet and AB5 alloy billet respectively. S02. Anneal the alloy billets obtained in step S01 to obtain AB2 alloy annealed material, BCC alloy annealed material and AB5 alloy annealed material. S03. The annealed alloy materials obtained in step S02 are pulverized to obtain the AB2 alloy powder, BCC alloy powder and AB5 alloy powder.
[0053] In some specific implementation schemes, in step S01, the melting temperatures of the AB2 alloy, BCC alloy, and AB5 alloy are 1400-1700℃, 1800-2200℃, and 1400-1600℃, respectively.
[0054] In some specific implementations, the AB2 alloy billet, BCC alloy billet, and AB5 alloy billet are each independently sheet material with a thickness of 0.3-0.5 mm.
[0055] In some specific implementations, step S02 includes: annealing the AB2 alloy billet under argon protection at 920-1020°C for 4-7 hours; annealing the BCC alloy billet under argon protection at 1200-1400°C for 1-5 hours; and annealing the AB5 alloy billet under argon protection at 900-1060°C for 4-8 hours.
[0056] In some specific implementations, in step S03, the pulverization process is ball milling or air jet milling under an inert atmosphere.
[0057] In some specific implementations, step S1 includes: S11. Mix AB2 alloy powder and BCC alloy powder under argon protection, and then ball mill the resulting mixed powder under argon protection to obtain a first coated intermediate; preferably, the maximum particle size of the first coated intermediate does not exceed 300 μm. S12. Anneal the first coated intermediate at 830-950℃ under argon protection for 1-3 hours to obtain AB2@BCC composite powder.
[0058] In some specific implementations, step S2 includes: S21. Mix AB2@BCC composite powder and AB5 alloy powder under argon protection, and then ball mill the resulting mixed powder under argon protection to obtain the second coated intermediate. S22. Anneal the second coating intermediate at 780-920℃ under argon protection for 0.5-2 hours to obtain the stepwise coating type AB2-based composite hydrogen storage alloy powder.
[0059] Another implementation scheme of this application is as follows: The application of any of the aforementioned step-coated AB2-based composite hydrogen storage alloys in the field of hydrogen storage includes any of the following: In scenario one, the composite hydrogen storage alloy is used for solid-state hydrogen storage; preferably, the composite hydrogen storage alloy is used for a metal solid-state hydrogen storage tank, or for a stationary hydrogen energy storage system, or for a mobile hydrogen energy vehicle; the mobile hydrogen energy vehicle is further preferably any one of a new energy vehicle, a hydrogen fuel cell vehicle, a hydrogen forklift, a hydrogen ship, a hydrogen train, or a hydrogen aircraft. Scenario 2: The composite hydrogen storage alloy is used in a hydrogen purification device; Scenario 3: The composite hydrogen storage alloy is used in a hydrogen compression storage device; Scenario 4: The composite hydrogen storage alloy is used in a portable hydrogen power source; Scenario 5: The composite hydrogen storage alloy is used in a power grid peak-shaving hydrogen energy storage system; Scenario 6: The composite hydrogen storage alloy is used in an integrated hydrogen production and storage system based on renewable energy.
[0060] In some specific implementations, the composite hydrogen storage alloy is used in the form of powder or molded body; the molded body is preferably an alloy block, alloy sheet or alloy ring formed by casting or pressing. Detailed Implementation
[0061] The raw materials used in this application can be purchased or synthesized in-house. The following specific embodiments are used to further describe the implementation of the present invention and do not limit the scope of the invention.
[0062] Example 1 This embodiment uses the following method to prepare a stepwise coated AB2-based composite hydrogen storage alloy: The composition of the AB2 alloy is designed to be Ti. 0.82 Zr 0.18 Mn 1.06 Cr 0.75Fe 0.05 The composition of BCC alloy is Ti 0.4 Cr 0.22 V 0.38 The composition of AB5 alloy is La 0.75 Ce 0.25 Ni 4.2 Co 0.3 Mn 0.42 Al 0.12 .
[0063] The weight ratio of the AB2 alloy, BCC alloy, and AB5 alloy is designed to be 95:3:2.
[0064] Preparation of alloy billets: The raw metal materials (purity ≥99.5%) were weighed according to the designed compositions of AB2, BCC, and AB5 alloys, and fed into three furnaces. Each furnace of raw materials was placed in a vacuum induction melting furnace, evacuated, and then filled with argon gas to a pressure of 0.05 MPa. Melting was carried out under argon protection. The melting temperature of AB2 alloy was 1600℃, BCC alloy was 2000℃, and AB5 alloy was 1500℃. The molten alloy liquid was continuously spun through water-cooled copper rollers to produce thin strip-shaped alloy billets with a thickness of 0.3–0.5 mm.
[0065] Annealing treatment of alloy billets: AB2 alloy billet was annealed at 960℃ for 6 h under argon protection atmosphere to obtain AB2 alloy annealed material; BCC alloy billet was annealed at 1300℃ for 2 h under argon protection atmosphere to obtain BCC alloy annealed material; AB5 alloy billet was annealed at 920℃ for 6 h under argon protection atmosphere to obtain AB5 alloy annealed material.
[0066] Crushing treatment of alloy annealed materials: AB2 alloy annealed material was ball-milled under an argon atmosphere and sieved to obtain AB2 alloy powder with a maximum particle size not exceeding 500 μm; BCC alloy annealed material was crushed by air jet milling under an argon atmosphere to obtain BCC alloy powder with a D50 of 10 μm; AB5 alloy annealed material was crushed by air jet milling under an argon atmosphere to obtain AB5 alloy powder with a D50 of 3 μm.
[0067] Primary coating and annealing: AB2 alloy powder and BCC alloy powder were weighed according to the designed weight ratio and added to a closed double-cone mixer, premixed for 30 min under argon protection. After mixing, the mixture was transferred to an argon atmosphere ball mill for grinding, so that the BCC fine powder was physically anchored on the surface of the AB2 alloy particles. Grinding was continued until the maximum particle size of the composite particles was less than 300 μm, obtaining a primary coating intermediate. The primary coating intermediate was placed under an argon atmosphere and annealed at 890℃ for 1.5 h. Low-temperature (far below the alloy melting point) solid-state diffusion was used to strengthen the interfacial bonding between the AB2 matrix and the BCC alloy, while retaining their respective independent crystalline phases, resulting in AB2@BCC composite powder.
[0068] Secondary coating and annealing: AB5 alloy powder was added to the AB2@BCC composite powder according to the designed weight ratio and placed in a closed double-cone mixer. The mixture was mixed for 30 min under argon protection, and then transferred to an argon-atmosphere ball mill for short-time grinding to uniformly disperse the AB5 ultrafine powder and adhere it to the outer surface of the AB2@BCC composite powder, obtaining a secondary coating intermediate. The secondary coating intermediate was then annealed at 840℃ for 1 h under an argon protective atmosphere to obtain a stepwise coated AB2-based composite hydrogen storage alloy (denoted as AB2@BCC@AB5) powder.
[0069] The AB2@BCC@AB5 alloy powder obtained in this embodiment was characterized by SEM and XRD.
[0070] SEM images of the samples ( Figure 1 The results show that the BCC-type hydrogen storage alloy and the AB5-type hydrogen storage alloy form island-like coatings on AB2. AB2 alloy serves as the matrix, with BCC and AB5 alloys dispersed and adsorbed on its surface. Specifically, some of the relatively larger BCC alloy particles are embedded in pits on the matrix surface, while others are dispersed and adsorbed on the flat surface of the matrix; the relatively smaller AB5 alloy particles are dispersed and adsorbed on both the AB2 matrix and the surface of the BCC particles.
[0071] XRD pattern of the sample ( Figure 2 The results show that the Laves phase diffraction peak of AB2 is the main phase, and the diffraction peaks of the BCC solid solution phase and the CaCu5 phase of AB5 are also detected, indicating that the three types of alloys retain their independent crystal structures after compositing. The diffraction peak intensities of the BCC phase and AB5 phase are relatively weak, which is consistent with the formulation design that the two phases have low contents in the composite hydrogen storage alloy (3 wt% and 2 wt% respectively in this embodiment).
[0072] Example 2 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 92:5:3; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0073] Example 3 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 94:4:2; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0074] Example 4 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 90:6:4; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0075] Example 5 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 97:2:1; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0076] Comparative Example 1 Following the preparation method of Example 1, instead of using BCC alloy and AB5 alloy, only AB2 alloy powder was prepared.
[0077] Comparative Example 2 Referring to the preparation method of Example 1, without using the BCC alloy, the weight ratio of AB2 alloy and AB5 alloy was set to 95:5; with the other conditions being the same, AB5 single-layer coated AB2-based composite hydrogen storage alloy (denoted as AB2@AB5) powder was obtained.
[0078] Comparative Example 3 Referring to the preparation method of Example 1, instead of using AB2 alloy, BCC alloy was used as the matrix, and the weight ratio of BCC alloy to AB5 alloy was set to 97:3; with the other conditions being the same, AB5 single-layer coated BCC-based composite hydrogen storage alloy (denoted as BCC@AB5) powder was obtained.
[0079] Comparative Example 4 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 91:7:2; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0080] Comparative Example 5 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 97:1:2; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0081] Comparative Example 6 Referring to the preparation method of Example 1, without using the AB5 alloy, the weight ratio of the AB2 alloy and the BCC alloy was set to 97:3; with the other conditions being the same, BCC single-layer coated AB2-based composite hydrogen storage alloy (denoted as AB2@BCC) powder was obtained.
[0082] Comparative Example 7 Referring to the preparation method of Example 1, the weight ratio of AB2 alloy, BCC alloy and AB5 alloy was changed to 92:3:5; the other conditions were the same, and AB2@BCC@AB5 alloy powder was obtained.
[0083] Example 6 In this embodiment, PCT tests were performed on the stepwise coated AB2-based composite hydrogen storage alloys (AB2@BCC@AB5) prepared in Examples 1-5 and the alloys prepared in Comparative Examples 1-7.
[0084] (1) Activation performance test The alloy powders prepared in each embodiment and comparative example were placed in a PCT testing apparatus and evacuated to 10 °C. -3 For activation, high-purity hydrogen gas (purity ≥ 99.999%) is introduced at 25℃ to a pressure of 5 MPa. The amount of hydrogen absorbed in each hydrogen absorption cycle is recorded, and the number of cycles in which more than 90% of the saturated hydrogen absorption capacity is first reached is recorded as the activation number. If activation is still not achieved after 30 cycles at room temperature, the temperature is increased to 50℃ and maintained for further testing. If activation is still not achieved after each 10℃ increase in temperature, activation is considered impossible.
[0085] (2) Hydrogen absorption capacity test The activated alloy powders were subjected to hydrogen absorption at 25°C and 5 MPa hydrogen pressure. After hydrogen absorption saturation, the saturated hydrogen absorption amount (wt%) was recorded. The hydrogen absorption amount was determined by volumetric method, and the value was obtained after subtracting the adsorption background of the container wall and the system. The average value of three parallel samples for each sample was taken as the final hydrogen absorption amount.
[0086] (3) Cyclic stability test At room temperature, each alloy powder was subjected to 100 hydrogen absorption-desorption cycles. In each cycle, the hydrogen absorption pressure was 5 MPa, and after hydrogen absorption to saturation, vacuum dehydrogenation was performed for 30 min. This cycle was repeated sequentially. The hydrogen absorption volume of the first cycle (initial hydrogen absorption volume) and the hydrogen absorption volume of the 100th cycle were recorded. The capacity retention rate (%) after 100 cycles was calculated using the following formula: Capacity retention rate after 100 cycles = (Hydrogen uptake in the 100th cycle / Hydrogen uptake in the 1st cycle) × 100% (4) Cost assessment Using the raw material cost of Comparative Example 1 (pure AB2 alloy) as a baseline (denoted as 100%), the relative costs were calculated based on the average market price of raw materials for AB2, BCC, and AB5 alloys in each example and comparative example, and their respective proportions. Among them, the cost of BCC alloy is significantly higher than that of AB2 alloy due to the presence of high-valence elements such as V, and the cost of AB5 alloy is also higher than that of AB2 alloy due to the presence of rare earth elements.
[0087] The test results for each embodiment and comparative example are shown in Table 1.
[0088] Table 1. Hydrogen storage performance test results
[0089] The AB2@BCC@AB5 alloys in Examples 1-5 all exhibited good overall hydrogen storage performance, specifically including: 5-12 activation cycles, hydrogen absorption of 1.83-1.95 wt%, and a capacity retention rate of 98.5%-99.2% after 100 cycles. Notably, Example 1 (AB2:BCC:AB5 = 95:3:2) required only 5 activation cycles, achieved a hydrogen absorption of 1.90 wt%, and a capacity retention rate of 98.8% after 100 cycles, while its cost was only 10% higher than that of the pure AB2 alloy.
[0090] Comparative Example 1 showed an activation count as high as 20 times, indicating that the pure AB2 alloy has a problem with activation difficulties.
[0091] Comparative Example 2 (AB2@AB5, without BCC) maintained a capacity retention of 97.0% after 100 cycles, lower than the 98.2% of the pure AB2 alloy. This indicates that a single layer of AB5 coating actually reduces cycle stability, thus demonstrating that BCC, as a defect-filling functional component, plays a crucial role in improving the cycle stability of AB2-based composite hydrogen storage alloys. Meanwhile, the high AB5 content (5 wt%) in Comparative Example 2 exacerbated the dilution effect of the AB5 alloy on hydrogen storage capacity (1.75 wt%).
[0092] Comparative Example 3 (BCC@AB5, without AB2) exhibited a high hydrogen absorption capacity of 2.21 wt%, but still required as many as 25 activation cycles. This indicates that using BCC as the matrix and coating AB5, even with the high capacity advantage of BCC, does not offer superior activation performance compared to the AB2 alloy. Furthermore, its raw material cost is 420% of that of the pure AB2 alloy, making it economically infeasible.
[0093] Comparative Example 6 (AB2@BCC, without AB5) had as many as 30 activation cycles, even higher than the 20 cycles of pure AB2 alloy, indicating that coating only BCC alloy cannot improve activation performance. This further proves that AB5 alloy, as a catalytic activation functional component, is indispensable for improving the activation performance of composite hydrogen storage alloys.
[0094] Compared with Example 1, Comparative Example 4 (high BCC content, 7 wt%) required 15 activation cycles, increasing the cost by 124%, indicating that excessive BCC reduces activation performance and increases costs; Comparative Example 5 (low BCC content, 1 wt%) had a limited effect on increasing hydrogen absorption, only 1.81 wt%; Comparative Example 7 (high AB5 content, 5 wt%) had a hydrogen absorption reduced to 1.79 wt%, indicating that excessive AB5 dilutes the overall hydrogen storage capacity.
[0095] All equivalent structural or procedural transformations made using the content of this application's specification, directly or indirectly applied to the same or related technical fields as this application, are included within the scope of patent protection of this application. For those skilled in the art, this invention can be implemented in a wide range with equivalent parameters, formulations, and conditions without departing from its spirit and scope, and without the need for unnecessary experimentation. Although this application provides specific embodiments, it should be understood that the conditions of the various embodiments can be combined in any suitable manner where technically feasible. To avoid unnecessary repetition, this application will not further describe the various possible combinations. In summary, any modifications, improvements, and other uses made using conventional techniques known in the art based on the principles of this invention are considered to be disclosed in this application.
Claims
1. A stepwise coated AB2-based composite hydrogen storage alloy, comprising a matrix and island-shaped coating layers; wherein the matrix is an AB2 alloy; and the island-shaped coating layers are composed of a BCC alloy and an AB5 alloy; wherein, The BCC alloy is partially or completely filled into the surface defects of the substrate.
2. The step-coated composite hydrogen storage alloy according to claim 1, characterized in that, The A-side element of the AB2 alloy is Ti, Zr or any combination thereof, and the B-side element is Mn, Cr, Fe, Ni, Co or any combination thereof. The BCC alloy is composed of V and any two or more of Ti, Zr, Nb, Mo, Hf, Cr, Fe, and Mn. The A-side element of the AB5 alloy is La, Ce, Pr, Nd or any combination thereof, and the B-side element is Ni, Co, Mn, Al, Fe, Cu or any combination thereof.
3. The step-coated composite hydrogen storage alloy according to claim 1, characterized in that, The general chemical formula of the AB2 alloy is Ti. (1-x) Zr x Mn a Cr b Fe c Where, 0.10≤x≤0.30, 0.80≤a≤1.20, 0.60≤b≤0.90, 0.05≤c≤0.15; The general chemical formula of the BCC alloy is Ti. α Cr β V γ Where, 0.3≤ α ≤0.4, 0.22≤ β ≤0.30, 0.30≤ γ ≤0.50; The general chemical formula of the AB5 alloy is La. (1 p) Ce p Ni t Co u Mn v Al w Where, 0.2≤ p ≤0.3, 3.8≤ t ≤4.2, 0.3≤ u ≤0.4, 0.3≤ v ≤0.4, 0.15≤ w ≤0.
25.
4. The step-coated AB2-based composite hydrogen storage alloy according to claim 1, characterized in that, The content of the AB2 alloy in the composite hydrogen storage alloy is 90-97 wt%; The BCC alloy content in the composite hydrogen storage alloy is 2-6 wt%. The content of the AB5 alloy in the composite hydrogen storage alloy is 1-4 wt%.
5. The preparation method of the stepwise coated AB2-based composite hydrogen storage alloy according to claim 1, comprising the following steps: S1. AB2 alloy powder and BCC alloy powder are mixed, pulverized and heat-treated sequentially under an inert atmosphere to obtain AB2@BCC composite powder; the heat treatment is carried out at a temperature lower than the melting points of the AB2 alloy and BCC alloy respectively. S2. The AB2@BCC composite powder and AB5 alloy powder are mixed, pulverized and heat-treated sequentially under an inert atmosphere to obtain the stepwise coated AB2-based composite hydrogen storage alloy powder; the heat treatment is carried out at a temperature lower than the melting points of the AB2 alloy, BCC alloy and AB5 alloy respectively. The weight ratio of the AB2 alloy powder, BCC alloy powder and AB5 alloy powder is (90-97):(2-6):(1-4), preferably 95:3:2, 92:5:3, 94:4:2, 90:6:4 or 97:2:1; The maximum particle size of the AB2 alloy powder does not exceed 500 μm; The D50 of the BCC alloy powder is 8-10 μm; The D50 of the AB5 alloy powder does not exceed 3 μm.
6. The preparation method according to claim 5, characterized in that, The AB2 alloy powder, BCC alloy powder, and AB5 alloy powder are obtained by the following methods: S01. The alloy raw materials are vacuum induction melted and shaped to obtain AB2 alloy billet, BCC alloy billet and AB5 alloy billet respectively. S02. Anneal the alloy billets obtained in step S01 to obtain AB2 alloy annealed material, BCC alloy annealed material and AB5 alloy annealed material. S03. The annealed alloy materials obtained in step S02 are pulverized to obtain AB2 alloy powder, BCC alloy powder and AB5 alloy powder. Preferably, in step S01, the melting temperatures of the AB2 alloy, BCC alloy, and AB5 alloy are 1400-1700℃, 1800-2200℃, and 1400-1600℃, respectively. Preferably, the AB2 alloy billet, BCC alloy billet, and AB5 alloy billet are each independently sheet material with a thickness of 0.3-0.5 mm; Preferably, step S02 includes: annealing the AB2 alloy billet under argon protection at 920-1020°C for 4-7 hours; annealing the BCC alloy billet under argon protection at 1200-1400°C for 1-5 hours; and annealing the AB5 alloy billet under argon protection at 900-1060°C for 4-8 hours. Preferably, in step S03, the pulverization process is ball milling or air jet milling under an inert atmosphere.
7. The preparation method according to claim 5, characterized in that, Step S1 includes: S11. Mix AB2 alloy powder and BCC alloy powder under argon protection, and then ball mill the resulting mixed powder under argon protection to obtain a first coated intermediate; preferably, the maximum particle size of the first coated intermediate does not exceed 300 μm. S12. Anneal the first coated intermediate at 830-950℃ under argon protection for 1-3 hours to obtain AB2@BCC composite powder.
8. The preparation method according to claim 5, characterized in that, Step S2 includes: S21. Mix AB2@BCC composite powder and AB5 alloy powder under argon protection, and then ball mill the resulting mixed powder under argon protection to obtain the second coated intermediate. S22. Anneal the second coating intermediate at 780-920℃ under argon protection for 0.5-2 hours to obtain the stepwise coating type AB2-based composite hydrogen storage alloy powder.
9. The application of the step-coated AB2-based composite hydrogen storage alloy of claim 1 in the field of hydrogen storage includes any one of the following: In scenario one, the composite hydrogen storage alloy is used for solid-state hydrogen storage; preferably, the composite hydrogen storage alloy is used for a metal solid-state hydrogen storage tank, or for a stationary hydrogen energy storage system, or for a mobile hydrogen energy vehicle; the mobile hydrogen energy vehicle is further preferably any one of a new energy vehicle, a hydrogen fuel cell vehicle, a hydrogen forklift, a hydrogen ship, a hydrogen train, or a hydrogen aircraft. Scenario 2: The composite hydrogen storage alloy is used in a hydrogen purification device; Scenario 3: The composite hydrogen storage alloy is used in a hydrogen compression storage device; Scenario 4: The composite hydrogen storage alloy is used in a portable hydrogen power source; Scenario 5: The composite hydrogen storage alloy is used in a power grid peak-shaving hydrogen energy storage system; Scenario 6: The composite hydrogen storage alloy is used in an integrated hydrogen production and storage system based on renewable energy.
10. The application according to claim 9, characterized in that, The composite hydrogen storage alloy is used in the form of powder or molded body; the molded body is preferably an alloy block, alloy sheet or alloy ring formed by casting or pressing.
Citation Information
Patent Citations
AB2-AB5 type composite hydrogen storage material as well as preparation method, equipment and application thereof
CN113528922A
Composite solid hydrogen storage material and preparation method thereof
CN114619026A
